On myself, and other, less important subjects - Hare, Caspar John, 1972- (Princeton University Press, 2009)
Caspar Hare makes an original and compelling case for "egocentric presentism," a view about the nature of first-person experience, about what happens when we see things from our own particular point of view. A natural thought about our first-person experience is that "all and only the things of which I am aware are present to me." Hare, however, goes one step further and claims, counterintuitively, that the thought should instead be that "all and only the things of which I am aware are present." There is, in other words, something unique about me and the things of which I am aware. On Myself a.